1-Deoxy-alpha-D-sorbopyranose - Jones, N; Fanefjord, M; Jenkinson, S; Fleet, G; Watkin, D (2006)
The crystalline form of 1-deoxy-o-sorbose, C6H 12O5, is shown to be 1-deoxy-α-D-sorbopyranose. This is the first reported crystal structure of a 1-deoxyketose. The absolute configuration was determined by the use of D-xylose as the starting material. The crystal structure has a three-dimensional hydrogen-bonded network. © 2006 International Union of Crystallography. All rights reserved.